Roderich MacFarquhar y Michael Schoenhals. Mao’s last revolution. Cambridge; Londres: The Belknap Press de Harvard University Press, 2006. xiii, 693 pp. - Cornejo, Romer (Estudios de Asia y África, 2007)
-